Peningkatan Minat Baca Pada Peserta Didik Sekolah Dasar Negeri 202/IX Bukit Makmur Kabupaten Muaro Jambi - Siti Nurkayati (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
Reading is a complex activity that directs large numbers of separate actions. One of the ways to achieve good reading success is interest. because without interest all activities will be carried out less effectively and efficiently. The reading interest of SDN 202 / IX Bukit Makmur students if observed as a whole is balanced or almost the same. However, it turns out that there are differences in reading interest between male and female students. The results of problem identification then emerged several problems at SDN 202 / IX Bukit Makmur which were identified as follows: (a) Students have not been seen to optimally utilize learning resources and learning facilities such as books and lessons, (b) students have not actively read books in the library. Based on the above problems, this research focuses on: Efforts made by classroom teachers to further increase the reading interest of class III students at SDN 202 / IX Bukit Makmur, Sei Bahar Sei Bahar District, Muaro Jambi Regency. This study aims to describe the teacher's efforts to increase reading interest in grade III SDN 202 / IX Bukit Makmur. This research is a descriptive qualitative research. The subjects of this study were 1 class teacher and 29 students III SDN 202 / IX Bukit Makmur. Data collection techniques using observation and interviews. Data analysis techniques in this study used data reduction, data presentation, and drawing conclusions. The results showed that the teacher's efforts to increase reading interest in third grade students of SDN 202 / IX Bukit Makmur, namely: (1) Encouraging children to tell stories about what they have heard or read, (2) Buying books that attract reading interest, (3) Swapping books with friends, (4) giving books as gifts, and (5) providing reading time. The reading interest of the third grade students was shown by the presence of several students visiting the library to borrow books or read books during recess.